Projections from IFPRI's IMPACT model: Climate change and food systems - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
Policymakers, analysts, and civil society face increasing challenges to reducing hunger and sustainably improving food security. Modeling alternative future scenarios and assessing their outcomes can help inform policy choices. The International Food Policy Research Institute’s IMPACT model is an integrated system of linked economic, climate, water, and crop models that allows for the exploration of such scenarios. Projections for 2030 and 2050, with and without climate change, cover food production, per capita consumption, net trade, and number of people at risk of hunger.